Dynamic Renal Deterioration in Flood-Associated Severe Leptospiral Multiorgan Dysfunction - Novilia Puspitasari; Donatila Mano S; Ita Murbani Handajaningrum (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Severe leptospirosis remains an under-recognized cause of rapidly progressive multiorgan dysfunction in tropical, flood-prone regions, where delayed risk stratification contributes to preventable renal failure and mortality. Acute kidney injury (AKI) represents a pivotal determinant of outcome, yet its clinical trajectory may be dynamic and misleading. This case report aimed to characterize the temporal clinical and biochemical progression of severe leptospiral infection complicated by Stage 3 AKI and to identify practical implications for early bedside recognition in endemic settings. We conducted a retrospective case report in accordance with CARE guidelines. Clinical, epidemiological, laboratory, and radiological data were systematically extracted from hospital records. Diagnosis was established based on compatible clinical manifestations, documented floodwater exposure with skin barrier disruption, positive serology, structured scoring using Modified Faine’s Criteria, and AKI staging according to KDIGO guidelines. Serial laboratory monitoring enabled assessment of organ involvement and disease evolution. The patient developed cholestatic jaundice, thrombocytopenia, pulmonary inflammatory changes, profound electrolyte imbalance, and rapidly progressive renal dysfunction fulfilling KDIGO Stage 3 criteria. Notably, transient improvement in serum creatinine preceded abrupt deterioration requiring hemodialysis, underscoring the non-linear course of leptospiral AKI. Integrated supportive management and tailored antimicrobial therapy resulted in subsequent stabilization. This report highlights the need for dynamic renal monitoring and early escalation strategies in high-risk patients with environmental exposure. Incorporating structured diagnostic scoring and continuous biochemical surveillance into frontline care may improve prognostic accuracy and reduce severe renal complications in climate-vulnerable populations.